PENGARUH KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA GURUâ (Studi Kasus Guru SMK di Kecamatan Margoyoso Kabupaten Pati) - Ubaidillah Wahab, 12 5202 0007; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to identify and analyze the influence of professional competence and job motivation mediated by job satisfaction who took the object of Vocational High School Teachers in Margoyoso Districk, Pati Regency. This research is explanatory research that aims to explain the variables that are relevant to the observed phenomena, this study also referred to the population study, the population used in this study is 143 people. Mechanical testing data used in this study include testing the validity of the factor analysis, validity and reliability tests with Cronbach alpha formula, before the data were analyzed research data on the test need to be tested is requiremens of the classical assumption.We use the three tests classical assumptionhere are normality test, multikolinieritas test, and heterosketastisitas test, multiple linear regression to know whether it effects or not between independent variables and dependent variables bound, the coefficient of determination is to find out how big is the effect of independent variables to the dependent variable, t test is to determine the feasibility of the model, hypothesis test is to answer whether the hypotesis is accepted or rejected. as well as regression testing mediation. The results show that professional competence has a positive and significant effect on job satisfaction. Job motivation variables have positive and significant impact for job satisfaction. Professional competence hasnât a positive and not significant effect on teacherâs performance. Job Motivation has a positive and significant effect on teacherâs performance. Job satisfaction has a positive and significant effect on teacherâs performance. Job satisfaction mediated the influence professional competence on teacherâs performance. And so job satisfaction mediated the influence job motivation on teacherâs performance. KeywordsÂ  :Â  Professional Competence, Job Motivation, Job Satisfaction, and Teacherâs Performance